Growth performance of lambs under intensive, continuous and rotational grazing systems of management - M.S. Ram prasad; S. Meenakshi Sundaram (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A trial was conducted to assess the growth performance of lambs under intensive, continuous and rotational grazing systems of management in indigenous ewe lambs, aged 4-5 months. They were randomly selected and allotted to three treatment groups: T1 (Intensive system – control), T2 (Rotational grazing) and T3 (Continuous grazing). The three treatment groups were compared for fortnightly bodyweight, average daily gain, fecal egg count (EPG). An artificial pasture was developed with Panicum maximum (Guinea grass), Stylosanthussp., Desmanthussp., and Cenchrusciliaris (Buffel grass) for the lambs under grazing systems. The Lambs under T1 were raised under stall fed system of management, the lambs under T2 were grazed under rotational grazing strategy in the four paddocks (2500 sq. ft. each) of plot-A while the lambs under T3 were continuously grazed in plot-B (10000 sq. ft.). At the end of the study period, statistical analysis revealed no significant difference between the treatment groups in fortnightly body weight as well as average daily gain (except for the fourth fortnight). However lambs under T2 had better mean fortnightly body weight and average daily gain. Significant differences were noticed in EPG (for Strongyle eggs) and biomass yield of fodder. Lambs under T2 had significantly (P=0.01) lower E.P.G. than T Plot-A under rotational grazing had significantly (P=0.01) higher fodder biomass yield and comparatively higher crude protein content than plot-B under continuous grazing. The results of this study pointed towards benefits in terms of lower EPG and better quantity and quality of biomass in rotational grazing compared to continuous grazing.